Diverse Effects of Natural and Synthetic Surfactants on the Inhibition of Staphylococcus aureus Biofilm - Gianna Allegrone; Chiara Ceresa; Maurizio Rinaldi; Letizia Fracchia (MDPI AG, 2021)
A major challenge in the biomedical field is the creation of materials and coating strategies that effectively limit the onset of biofilm-associated infections on medical devices. Biosurfactants are well known and appreciated for their antimicrobial/anti-adhesive/anti-biofilm properties, low toxicity, and biocompatibility. In this study, the rhamnolipid produced by Pseudomonas aeruginosa 89 (R89BS) was characterized by HPLC-MS/MS and its ability to modify cell surface hydrophobicity and membrane permeability as well as its antimicrobial, anti-adhesive, and anti-biofilm activity against Staphylococcus aureus were compared to two commonly used surfactants of synthetic origin: Tween® 80 and TritonTM X-100. The R89BS crude extract showed a grade of purity of 91.4% and was composed by 70.6% of mono-rhamnolipids and 20.8% of di-rhamnolipids. The biological activities of R89BS towards S. aureus were higher than those of the two synthetic surfactants. In particular, the anti-adhesive and anti-biofilm properties of R89BS and of its purified mono- and di-congeners were similar. R89BS inhibition of S. aureus adhesion and biofilm formation was ~97% and 85%, respectively, and resulted in an increased inhibition of about 33% after 6 h and of about 39% after 72 h when compared to their chemical counterparts. These results suggest a possible applicability of R89BS as a protective coating agent to limit implant colonization.